Domination by aggressive behaviours among students in Orumba North, Anambra State, Nigeria (2018)
This study adopted descriptive survey design to investigate the influence of gender, parenting styles and peer pressure on the aggressive behavours of students in Orumba North local government area of Anambra State. Two hundred and ninety-one students consisting 189 males and 102 females with age range of 13 to 16 and mean age of 14.6 years were randomly drawn with ballot method from a population of students spread across three community secondary schools in ONLGAs. Three instruments namely; Buss-Perry Aggression Questionnaire (r=0.72); Baumrid Parental Care Scale (r=0.70); Glasen and Brown Peer Pressure Inventory (r=0.78) were employed for collection of data. T-test for independent samples and Pearson’s Product Moment Correlation (PPMC) were adopted as statistical tools to analyze four hypotheses at 0.05 level of significance. The results show that level of aggressive behaviour differs significantly on the basis of gender (df=289, t=2.9908, P<.05). There is a significant negative relationship between parenting styles and aggressive behaviours (r=-0.074, p>0.05)., while positive association exist between peer pressure and aggressive behaviour (r=0.6296, p<0.05). The independent variables jointly contributed 52% of the variance in aggressive behaviours among students in ONLGA. The researchers concluded that both personal and social factors are related with aggressive behaviours of students. It recommended that counselling psychologists should mount interventions to teach parents positive parenting styles as well as empower the students with the skill of anger management.